ANALISIS BUTIR SOAL PILIHAN GANDA MATERI NILAI-NILAI KRISTIANI MENJADI PEGANGAN HIDUPKU UNTUK KELAS VII SMP NEGERI 1 NABIRE - Marzel Joska Hitipeuw; Alfrida Balisa; Yonece Delila Mara; Wawan Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning evaluation plays a strategic role in measuring the achievement of educational objectives and serves as a basis for improving the learning process. In the context of Christian Religious Education, evaluation focuses not only on cognitive aspects but also on the internalization of Christian values ​​as a guide to life, thus requiring high-quality and tested instruments. This study aims to analyze the quality of multiple-choice questions on the topic "Christian Values ​​as My Lifeline" for seventh-grade students at SMP Negeri 1 Nabire, in terms of validity, discriminating power, and difficulty level. This study used a quantitative approach with a descriptive-evaluative approach. The subjects were seventh-grade students selected using purposive sampling. The instrument consisted of 25 multiple-choice questions with five answer alternatives. Data collection was conducted through a learning achievement test, while data analysis included validity testing using product-moment correlation, discriminating power analysis, and difficulty level analysis. The results showed that most of the items were of fairly good quality. A total of 15 items were declared valid and 10 were invalid, indicating that the instrument adequately represented the learning indicators, although some still needed improvement. The discriminatory power of the items was in the fair to good category, with a small number of items not being able to optimally differentiate student abilities. The difficulty level was predominantly in the moderate and easy categories, indicating a relatively balanced distribution of item difficulty and appropriateness for learning evaluation. These findings contribute to the development of more effective evaluation instruments, particularly for values-based learning. The study's conclusions indicate that the test instrument is of suitable quality for use in learning evaluation, but requires revision to items that are invalid and have low discriminatory power. This study recommends the importance of ongoing item analysis to improve evaluation quality and encourages further research that integrates reliability analysis and a more comprehensive measurement approach.